2020
DOI: 10.1186/s13063-020-04630-6
|View full text |Cite
|
Sign up to set email alerts
|

Prednisone for patients with recurrent implantation failure: study protocol for a double-blind, multicenter, randomized, placebo-controlled trial

Abstract: Background Recurrent implantation failure (RIF) brings great challenges to clinicians and causes deep frustration to patients. Previous data has suggested that prednisone may play a promising role in the establishment of pregnancy and help improve the pregnancy outcome in women with RIF. But there is insufficient evidence from randomized clinical trials that had adequate power to determine if prednisone can enhance live births as the primary outcome. Methods/design This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 23 publications
(26 reference statements)
0
9
0
Order By: Relevance
“…Several studies indicate that prednisone may be highly beneficial in treating patients with RIF [ 20 ]. A 2020 study found that prednisone can affect pregnancy outcomes in patients with RIF [ 21 ]. The in vitro studies reveal that progesterone may inhibit TNF-α-induced apoptosis [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies indicate that prednisone may be highly beneficial in treating patients with RIF [ 20 ]. A 2020 study found that prednisone can affect pregnancy outcomes in patients with RIF [ 21 ]. The in vitro studies reveal that progesterone may inhibit TNF-α-induced apoptosis [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other treatment hypotheses might be valid and some RCTs are ongoing in order to test them. In this context, of particular relevance is the study protocol published by Lu et al 179 . Authors aim to determine if prednisone can enhance live birth in women with RIF undergoing IVF.…”
Section: Discussionmentioning
confidence: 99%
“…Authors aim to determine if prednisone can enhance live birth in women with RIF undergoing IVF. Interestingly, studies have shown that prednisone could not only suppress the inflammatory response in pre-implantation endometrium, but also stimulate the secretion of hCG and promote proliferation and invasion of trophoblast 179 . The efficacy of ad hoc treatments in women with known diseases and RIF also deserves to be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical pregnancy rate in the prednisolone group was significantly higher (48.3% vs. 29.6%), although livebirth rates were not reported. Another randomised trial of prednisolone in women with RIF has been registered and results are awaited 60 …”
Section: Discussionmentioning
confidence: 99%
“…Another randomised trial of prednisolone in women with RIF has been registered and results are awaited. 60 Immune therapy in reproductive medicine has a long history of excessive claims to be 'the answer' and equally excessive counter claims that it is 'useless' . The reality is that it is, at best, just one possible factor out of many that influence the outcome of IVF.…”
Section: Discussionmentioning
confidence: 99%